Inter- and Intra-observer Reproducibility of Thyroid Fine Needle Aspiration Cytology: An investigation of Bethesda 2023 Using Immunohistochemical BRAFV600E Antibody - Erdogan Bahattin; Dündar Emine; Çetin Kısmet Çivi; Yılmaz Fatih (Journal of Cytology)
Background: The Bethesda System for Reporting Thyroid Cytology (TBSRTC) recommended for the interpretation of needle aspiration cytology of the thyroid, is the most widely used worldwide. Studies have shown that the disagreement between observers, especially in the Bethesda III and IV diagnostic categories, is not insignificant at 10%–40%. In the TBSRTC 2023 version, some definitions were removed and simplified, and molecular pathology was proposed as a complement to cytopathology. The current availability of molecular tests is limited because they can be performed in a few centers and are expensive. Therefore, our study investigated intra- and inter-observer agreement according to TBSRTC 2023 using only immunohistochemically BRAFV600E antibodies. Materials and Methods: The study included 173 cases with aspiration cytology evaluated between 2019 and 2022. The immunohistochemical procedure applied BRAFV600E (RM8) monoclonal antibody to cell block sections. All slides were assessed and categorized by three different observers. Data were interpreted using Cohen’s kappa and Fleiss’s kappa test in the Statistical Package for Social Sciences Windows 2021 program. Results: For the applied RM8 antibody, sensitivity was 64.71% and specificity was 87.27%. In terms of diagnostic categories, inter-observer agreement was good for Bethesda II (K = 0.606) and moderate for Bethesda III (K = 0.429), Bethesda IV (K = 0.523), Bethesda V (K = 0,464), and Bethesda VI (K = 0.544), respectively. Conclusion: In conclusion, the study reveals that the 2023 version of TBSRTC provides improvement, especially in the categories of uncertain diagnosis, but is still insufficient to improve cytological diagnostic accuracy, at which point molecular analyses become even more important.